A randomized trial of risk‐adapted screening for prostate cancer in young men—Results of the first screening round of the PROBASE trial. Issue 11 (17th February 2022) - Arsov, Christian; Albers, Peter; Herkommer, Kathleen; Gschwend, Jürgen; Imkamp, Florian; Peters, Inga; Kuczyk, Markus; Hadaschik, Boris; Kristiansen, Glen; Schimmöller, Lars; Antoch, Gerald; Rummeny, Ernst; et al.
Abstract: There is no generally accepted screening strategy for prostate cancer (PCa). From February 2014 to December 2019 a randomized trial (PROBASE) recruited 46 642 men at age 45 to determine the efficacy of risk‐adapted prostate‐specific antigen‐based (PSA) screening, starting at either 45 or 50 years. PSA tests are used to classify participants into a low (<1.5 ng/mL), intermediate (1.5‐2.99 ng/mL) or high (≥3 ng/mL) risk group. In cases of confirmed PSA values ≥3 ng/mL participants are recommended a prostate biopsy with multiparametric magnetic resonance imaging (mpMRI). Half of the participants (N = 23 341) were offered PSA screening immediately at age 45; the other half (N = 23 301) were offered digital rectal examination (DRE) with delayed PSA screening at age 50. Of 23 301 participants who accepted baseline PSA testing in the immediate screening arm, 89.2% fell into the low, 9.3% into intermediate, and 1.5% (N = 344) into the high risk group. Repeat PSA measurement confirmed high‐risk status for 186 men (0.8%), of whom 120 (64.5%) underwent a biopsy. A total of 48 PCas was detected (overall prevalence 0.2%), of which 15 had International Society of Uropathology (ISUP) grade 1, 29 had ISUP 2 and only 4 had ISUP ≥3 cancers. In the delayed screening arm, 23 194 participants were enrolled and 6537 underwent a DRE with 57 suspicious findings, two of which showed PCa (both ISUP 1; detection rate 0.03%). In conclusion, the prevalence of screen‐detected aggressive (ISUP ≥3) PCa in 45‐year‐old men is very low. DRE did not turn out effective for early detection of PCa. Abstract : What's new? The German Prostate Cancer Early Detection Study Based on a Baseline PSA Value in Young Men (PROBASE) is the largest risk‐adapted screening trial in prostate cancer. It is based on the observation that the baseline prostate specific antigen (PSA) level at age 45‐50 is strongly predictive of a man's risk of developing advanced prostate cancer years later. The results of the first screening round showed a low prevalence (0.2%) of prostate cancer in 45‐year‐old men when risk‐stratifying with PSA levels, with only 0.02% of aggressive cancers. In comparison, digital rectal examination showed low effectiveness for early detection of prostate cancer.